Para além dos holofotes: uma análise da gestão de carreira musical - Claudio Pereira de Almeida (2018)
This study aims to point out processes from the world of entrepreneurship and administration, suggesting its indispensability in the construction of self - sustaining musical careers. The data cross from the researched authors constitutes the major contribution of this research, so that the relevant literature analysis is interlaced with information about three rock bands from the city of Belo Horizonte, obtained from interviews, local observations, audiovisual records and documentary analysis. Behavioral tendencies, gaps in the professional musician's training process and possibilities for deepening the theme are highlighted, emphasizing the importance of developing an entrepreneurial mindset for the music professional